Des méthodologies à repenser pour qualifier et analyser les territoires et les paysages ordinaires - Élise Temple‑Boyer (Bulletin de l’Association de Géographes Français)
Even as ordinary landscapes are currently introduced in operations of environmental policies, their analysis and characterization is difficult since these territories are usually examined as the opposite of labeled territories. Ordinary territories cannot be analyzed on a segmented approach, which is the current basis of environmental policies where protection and conservation frameworks are inoperative. That is why it is important to propose new methods for the analysis of these spaces highlighting local space and local stakeholders. Ordinary landscapes then emerge as new laboratories of environmental governance, where local actors are fully involved and part of the innovation process. To avoid the zoning issue and to better grasp the dynamics and stakes of ordinary landscapes, an analysis combining transect data and gradients can be deployed. Through this approach, peri-urban fringes highlight particularly these ordinary landscapes since they are most of the time unprotected spaces, subject to powerful dynamics of territorial evolution, without much consensus in their management, especially in the Paris Region.